Anthony Seeger’s Contribution to Ethnomusicology: A Bio-Bibliography of the Why Suyá Sing’s (1987) Author - Indrawan, Andre (Institut Seni Indonesia Yogyakarta, 2019)
This research is a bio-bibliographical study of an American ethnomusicologist, Anthony Seeger. Issues discussed include seeking information about Seeger as an important figure, his contribution to scientific development, music education, music history, and basic knowledge of ethnomusicology. Since the data are in the form of written sources that not only come from his works but also the works of others who cite his works so that literature review is used as a research method to obtain answers to the problems raised. This study concluded that the anthropological approach greatly influenced the characteristics of Seeger’s field research in studying the Suyá’s music in the interior part of Brazil. The report from the research turned out to be an essential source for the development of Seeger’s theories of musical anthropology. From the success of Seeger, we could learn how important fieldwork is in ethnomusicology. Kontribusi Anthony Seeger Terhadap Etnomusikologi: Sebuah Bio-Bibliografi Pengarang The Why Suya’ Sing (1987). Penelitian ini adalah studi bio-bibliografi seorang etnomusikolog Amerika, Anthony Seeger. Masalah yang dibahas termasuk mencari informasi tentang Seeger sebagai tokoh penting, kontribusinya terhadap pengembangan ilmiah, pendidikan musik, sejarah musik, dan pengetahuan dasar tentang etnomusikologi. Karena semua data tersebut dalam bentuk sumber tertulis yang tidak hanya berasal dari karya-karyanya tetapi juga karya-karya orang lain yang mengutip karya-karyanya, sehingga tinjauan pustaka digunakan sebagai metode penelitian untuk mendapatkan jawaban atas masalah yang diajukan. Studi ini menyimpulkan bahwa pendekatan antropologis sangat mempengaruhi karakteristik penelitian lapangan Seeger dalam mempelajari musik Suyá di bagian interior Brasil. Laporan dari penelitian ini ternyata menjadi sumber penting untuk pengembangan teori antropologi musikal Seeger. Dari keberhasilan Seeger, kita bisa belajar betapa pentingnya kerja lapangan dalam etnomusikologi.Kata kunci: etnomusikologi; kerja lapangan; antropologi musikal; Seeger; Suyá